Kolaborasi Guru, Orang Tua Dan Masyarakat Sekolah Dalam Pembentukan Karakter Siswa Melalui Pendidikan Agama Islam - Munawaroh, Lailatul (Abnauna: Jurnal Ilmu Pendidikan Anak, 2025)
ABSTRACT The difficulty of developing religious character in students in this modern era has become the main goal of previous researchers to explain the important role of religious teachers, what strategies should be used, and the benefits of teacher, parent and school community contributions in the process of forming students' religious character. The purpose of this study is to identify the role of Islamic Religious Education teachers, strategies carried out by teachers and collaboration between teachers, parents and the school community in forming good character in students. The type of method used is a Systematic literature review (SLR). This study utilizes Garba Rujukan Digital (Garuda), a repository of Indonesian scientific articles, as a data source. In this study, the author analyzed 5 articles that met the criteria, namely written in Indonesian and published in the 2014-2024 period. The article search was carried out using three main keywords: "character formation", "Islamic religious education", and "teacher role". The article search strategy used keywords; character formation, Islamic Religious Education and the role of Islamic Religious Education teachers. The analysis technique used in this study was the content analysis technique. The results of the study revealed that Islamic Religious Education teachers play an important role in the process of forming religious characters that students must have and are assisted by various strategies to facilitate the formation of student characters, as well as contributions between parents and the school community are important in instilling these religious characters. Keywords: role of teachers, religious character, Islamic religious education   ABSTRAK Sulitnya menumbuhkan karakter reliugius pada diri siswa di era modern ini menjadi tujuan utama para peneliti terdahulu untuk menjelaskan peran penting guru agama, stratetegi apa yang harus digunakan, serta manfaat adanya kontribusi guru, orang tua dan masyarakat sekolah dalam proses pembentukan karakter religius siswa. Tujuan dari penelitian ini adalah untuk mengidentifikasi peran guru PAI, Srategi yang dilakukan guru serta kolaborasi antar guru orangtua dan masyarakat sekolah dalam membentuk karakter baik siswa, Jenis metode yang digunakan adalah Systematic literature review (SLR). Penelitian ini memanfaatkan Garba Rujukan Digital (Garuda) yakni sebuah repositori artikel ilmiah Indonesia, sebagai sumber data. Dalam penelitian ini, penulis menganalisis 5 artikel yang memenuhi kriteria yaitu ditulis dalam bahasa Indonesia dan dipublikasikan pada rentang waktu 2014-2024. Pencarian artikel dilakukan menggunakan tiga kata kunci utama: "pembentukan karakter", "pendidikan agama Islam", dan "peran guru". Strategi pencarian artikel menggunakan kata kunci; pembentukan karakter, Pendidikan Agama Islam dan peran guru PAI. Teknik analisis yang digunakan pada penelitian ini adalah teknik analisis isi. Hasil penelitian mengungkapkan bahwa guru PAI berperan penting dalam proses pembentukan karakter religius yang harus dimiliki siswa dan dibantu dengan berbagai strategi-starategi untuk mempermudah pembentukan karakter siswa, begitu juga dengan kontribusi antar orang tua dan masyarakat sekolah merupakan hal penting dalam menanamkan karakter religius tersebut. Kata Kunci: peran guru, karakter religius, Pendidikan agama islam